Measurement of Longevity Risk of Life Annuity Based on C-ROSS Framework. (18th September 2020) - Zhao, Ming; Li, Ziwen; Cai, Yinge; Li, Weiting
Abstract : This paper constructs a model to measure longevity risk and explains the reasons for restricting the supply of annuity products in life insurance companies. According to the Lee–Carter Model and the VaR-based stochastic simulation, it can be found that the risk margin of the first type of longevity risk for ignoring the improvement of mortality rate is about 7%, and the risk margin of the second type of longevity risk for underestimating mortality improvement is about 7%. Therefore, the insurer needs to use cohort life table pricing premium and gradually prepares longevity risk capital during the insurance period.